La retórica del deseo en los relatos de viaje a Tierra Santa - Chad Leahy (Criticón, 2017)
This article argues that the representation of “desire” in accounts of travel to the Holy Land written in the 16th and 17th centuries in Spain is subordinated to a series of rhetorical strategies whose operation has gone largely unnoticed by critics until now. These strategies aim at satisfying very concrete spiritual and material objectives and should be considered a key aspect of such texts, allowing us a better historized interpretation of one of the most popular genres of the period.